1996
DOI: 10.1016/s0022-5347(01)66298-0
|View full text |Cite
|
Sign up to set email alerts
|

Priapism Associated with Sickle Cell Hemoglobinopathy in Children: Long-Term Effects on Potency

Abstract: Shunts performed within 48 hours, especially in postpubertal children, seemed more likely to preserve potency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
1
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 21 publications
0
29
1
2
Order By: Relevance
“…More invasive approaches such as surgery to decompress the corpora cavernosa are restricted to the refractory acute attacks. (11,14). The recurrence of the acute episodes is common.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More invasive approaches such as surgery to decompress the corpora cavernosa are restricted to the refractory acute attacks. (11,14). The recurrence of the acute episodes is common.…”
Section: Discussionmentioning
confidence: 99%
“…Finasteride is currently considered an alternative prophylactic treatment for recurrent priapism in adults (6,12,14). This drug acts by inhibiting the type 2 isoform of the 5 alpha-reductase enzyme, which is responsible for the conversion of testosterone into dihydrotestosterone predominantely in hair follicles and the prostate (6).…”
Section: Discussionmentioning
confidence: 99%
“…Children with sickle cell anemia [3] are at a higher risk of developing erectile dysfunction. Interestingly, Dewan et al [25] reported that among children with sickle cell anemia-associated priapism, restoration of potency was 100% with conservative treatment, whereas it was only 27% with surgical management.…”
Section: Discussionmentioning
confidence: 99%
“…Spontaneous priapism in adults is predominantly (75%) of idiopathic origin, whereas in children, sickle cell anemia is the leading cause (67%) of it [2]. About 6% of children with sickle cell anemia are complicated with priapism [3]. It is estimated that 80% to 98% of children with sickle cell anemia develop at least one episode of priapism before 20 years of age [4].…”
mentioning
confidence: 99%
“…O prognóstico pode ser melhor para pré-púberes 20 . Não conseguimos encontrar explicações para esse fenômeno, mas talvez a ausência de atividade androgênica pudesse explicar a proteção relativa de pacientes antes da puberdade.…”
Section: Prognósticounclassified